Optimization of the posterior method of dissection of the anatomical components of the abdominal wall for postoperative ventral hernias of giant sizes - Feleshtynskyi, Y.; Marshtupa, O.; Antoniv, V. (Journal of Education, Health and Sport, 2023)
The aim of the work - to increase the effectiveness of surgical treatment of PVH of giant size by using the improved TAR technique. Materials and methods. An analysis of the surgical treatment of 150 patients with post-operative abdominal hernias of giant size, who underwent posterior techniques of disconnection of the anatomical components of the abdominal wall TAR in combination with alloplasty, was performed in the period from 2016 to 2022. The main group consisted of 74 patients with post-operative ventral hernias of giant size who underwent advanced TAR technique in combination with IPOM alloplasty. The comparison group consisted of 76 patients with giant PVH who underwent the classic posterior technique of component separation TAR in combination with retromuscular alloplasty. Results of the studies and their discussion The results of ICP measurement in patients of the main group showed that after 6-24 hours after the operation in 73 (98.6%) patients, ICP was within 7.1 ± 1.3 mmHg and only 1 (1.4%) patient had IAH of the first degree, which was caused by intestinal paresis. After conservative treatment and elimination of intestinal paresis, after 48 hours ICP was 5.7 mmHg which was normal. In 76 patients of the comparison group who underwent classic TAR with retromuscular alloplasty, IAH of varying degrees of severity was diagnosed in 6 (7.9%) patients. Among them, 3 (3.9%) patients developed IAH of the I degree, 2 (2.6%) had IAH of the II degree and 1 (1.3%) patient had IAH of the III degree.